OPTIMASI PRODUKSI HORMON, NITROGEN TOTAL DAN KEPADATAN SEL AZOTOBACTER PADA INOKULAN CAIR MELALUI PENAMBAHAN Fe DAN Mo - Danapriatna, Nana; Hutagalung, Benny; Hindersah, Reginawati (Jurnal Agroteknos, 2013)
Production of liquid biofertilizer Azotobacter requires pure inoculum with N2 fixation capacity, hormone production, and optimal cell density. This research was conducted to determine the effect of Fe-Mo microelement and Azotobacter inoculant concentration on enhancement of hormones and total nitrogen content as well as Azotobacter population in liquid culture. The experiment used Randomized Completely Design with six treatments and three replications. The treatments were combination of inoculant concentration (without, 5%, 10% and 15%) and Fe-Mo solution (with and without Fe-Mo). The result showed that addition of Fe and Mo microelements in liquid culture increased Cytokinin production as well as population density of Azotobacter. Inoculant concentration of 10% with the addition of micronutrients Fe and Mo was able to optimize the production of hormones, nitrogen fixation, and cell density of Azotobacter. Keywords : Fe, Mo, Total Nitrogen, Hormone, Azotobacter